(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Maps of science, particularly those using bibliographic data, have become more popular in the past decades. There is substantial increase of bibliometric maps of science thanks to more data becoming available, computer becoming more powerful and technology becoming more useable in this context. Keywords: Mapping Science. Networks. VOSviewer. Link para o texto completo (PDF) http://seer.ufrgs.br/index.php/EmQuestao/article/view/36194/23771